Influence of institutional pressures on the adoption of green initiatives - Abdul Aziz, Nor Azah; Senik, Rosmila; Foong, Soon Yau; Ong, Tze San; Attan, Hassan (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Environmental issues which have negative impacts on environment, social, and economy, imply a need for sustainability practices. As the concept of sustainability is broad, this study focuses only on the environmental aspect, particularly green practices. It aims to examine the influence of institutional pressures, namely coercive, mimetic, and normative pressures on the adoption of green initiatives, and the extent of green adoption in Malaysian public listed companies (PLCs). A questionnaire survey was conducted on all 921 PLCs in Bursa Malaysia. The data from 120 usable questionnaires were analysed using partial least square structural equation modelling (PLS-SEM). The findings indicate that the adoption of green initiatives in PLCs is significantly influenced by coercive and normative pressures, while mimetic pressure does not influence the adoption of green initiatives in PLCs. Theoretically, this study contributes to management accounting and environmental management literatures in the context of green practices towards environmental sustainability. It also provides empirical evidence to practitioners on the need to understand the key drivers of green initiatives for them to meet the challenges on green issues and to derive the best results from implementation of the initiatives. Regulatory authorities or policy makers may facilitate more extensive adoption of green initiatives by providing more financial incentives for technical resources and training.